Genetic and Environmental Effects on Gene Expression Signatures of Blood Pressure: A Transcriptome-Wide Twin Study. Issue 3 (March 2018) - Huang, Yisong; Ollikainen, Miina; Sipilä, Pyry; Mustelin, Linda; Wang, Xin; Su, Shaoyong; Huan, Tianxiao; Levy, Daniel; Wilson, James; Snieder, Harold; Kaprio, Jaakko; Wang, Xiaoling
Abstract : Recently, 2 transcriptome-wide studies identified 40 genes that were differentially expressed in relation to blood pressure. However, to what extent these BP-related gene expression signatures and their associations with BP are driven by genetic or environmental factors has not been investigated. In this study of 391 twins (193 twin pairs and 5 singletons; age 55–69 years; 40% male; 57% monozygous) recruited from the Finnish Twin Cohort, transcriptome-wide data on peripheral leukocytes were obtained using the Illumina HT12 V4 array. Our transcriptome-wide analysis identified 1 gene ( MOK [MAPK/MAK/MRK overlapping kinase], P =7.16×10 − 8 ) with its expression levels associated with systolic BP at the cutoff of false-discovery rate <0.05. This association was further replicated in the Framingham Heart Study ( P =1.02×10 − 5 ). Out of the 40 genes previously reported, 12 genes could be replicated in the twin cohort with false-discovery rate <0.05 and consistent direction of effect. Univariate twin modeling showed that genetic factors contributed to the expression variations of 12 genes with heritability estimates ranging from 6% to 65%. Bivariate twin modeling showed that 53% of the phenotypic association between systolic BP and MOK expression, and 100% of the phenotypic association of systolic and diastolic BP with CD97 (cluster of differentiation 97), TIPARP (TCDD-inducible poly[ADP-ribose] polymerase), and TPPP3 expression could be explained by genetic factors shared in common. In this study of adult twins, we identified one more gene, MOK, with its expression level associated with BP, and replicated several previously identified signals. Our study further provides new insights into the genetic and environmental sources of BP-related gene expression signatures. Abstract : Supplemental Digital Content is available in the text.